Electrodynamics Model of the Gravitational Interaction - M. Ja. Ivanov; E. M. Ivanova (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
The analyzed model of the gravitational interaction is based on Coulomb’s law, Maxwell’s electrodynamics, and on the extremely small difference in the distribution of potentials near the "point" electric charges in the centers of the proton and electron. Such an extremely small difference in the distribution of electric potentials near the centers of different diameters (and masses) of the proton and electron leads to the presence of a small total positive charge in a body of baryonic matter, which by definition is directly proportional to its baryonic mass. The presence of this charge generates a force interaction in the external space surrounding the baryonic bodies. The gravitational process is described by the mutual influence of electrostatic forces determined by the potential gradient and the gradient of the gas dynamic pressure for the external medium. A mathematical description of such a model of the gravitational interaction is given by the Poisson equation (for the stationary case) with the corresponding boundary conditions. The propagation of a force field in free space is given by a system of extended Maxwell equations. The gravitational frequency (similar to the known plasma frequency), the corresponding gravitational time period, and the characteristic linear size of space are determined. In this model, the equality of the inertial and gravitational masses is a consequence of the original equations. An analytical solution is obtained for the structure of black holes and for cosmic jets from their center.